1992
DOI: 10.1109/10.135539
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach to modeling the backscattered Doppler ultrasound from blood

Abstract: A unified approach to modeling the backscattered Doppler ultrasound signal from blood is presented. The approach consists of summing the contributions from elemental acoustic voxels each containing many red blood cells (RBC's). For an insonified region that is large compared to a wavelength, it is shown that the Doppler signal is a Gaussian random process that arises from fluctuation scattering, which implies that the backscattered power is proportional to the variance of local RBC concentrations. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 33 publications
1
59
0
6
Order By: Relevance
“…Therefore, ultrasound scattering mainly results from the mismatches in the mechanical properties of continuous and particle phases. Theoretical models of ultrasound scattering are based either on the continuum approach [23,24] or the particle approach [12,13,22]. The continuum approach recognizes that particles separated by less than λ/2 cannot be resolved by the transducer and therefore the suspension can be modeled as a continuum medium in which local fluctuations in density and compressibility give rise to the scattered waves [23].…”
Section: Ultrasonic Scattering From a Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ultrasound scattering mainly results from the mismatches in the mechanical properties of continuous and particle phases. Theoretical models of ultrasound scattering are based either on the continuum approach [23,24] or the particle approach [12,13,22]. The continuum approach recognizes that particles separated by less than λ/2 cannot be resolved by the transducer and therefore the suspension can be modeled as a continuum medium in which local fluctuations in density and compressibility give rise to the scattered waves [23].…”
Section: Ultrasonic Scattering From a Suspensionmentioning
confidence: 99%
“…In the concentrated regime, particles or clusters can no longer be considered as independent and correlation effects influence the scattered power because of wavelets interference arising from a dense distribution of scatterers [10]. The scattered power can be considered as the result of imperfect wave destruction either associated with a packing factor [12,22] or with the variance in local scatterer concentration [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for the phenomenon has been well analyzed and explained by the theoretical models (Lucas and Twersky, 1987;Mo and Cobbold, 1992;Bascom and Cobbold, 1995), which show that the scattering from a packed distribution of small scatterers is related to fluctuation of the number and size of the scatterers in a volume rather than the number itself. Experimental reports from RBC suspension by Cloutier et al (1995Cloutier et al ( , 1996Cloutier et al ( , 2000 showed that flow turbulence downstream from a stenosis resulted in increased Doppler power.…”
Section: Review Papermentioning
confidence: 99%
“…A nonlinear relationship between hematocrit and ultrasonic backscatter of RBC suspension was experimentally found and the results were in excellent agreement with the theoretical models which predict a scattering maximum peak at 13-20 % hematocrit (Shung et al 1976;Shung 1988a, 1988b). Later, the packing theory was extended to the continuum model and the particle and continuum models were unified as a hybrid model (Mo and Cobbold, 1992). According to the theory, it was postulated that ultrasound backscatter should be sensitive even to a small degree of RBC aggregation.…”
Section: Scattering Of Ultrasound By Bloodmentioning
confidence: 99%
“…However, although the simulations/models of Doppler signals from blood have been developed over many years and have characteristics very similar to real signals [4][5][6][7][8][9][10][11] wall signal models are relatively crude -single sinusoids or random signals. A simulator is required that generates a Doppler signal as from blood and vessel wall, having controllable characteristics similar to those found in practice.…”
Section: Introductionmentioning
confidence: 99%